Similar mentality and perception in the context of contemporary Ukraine-Poland relations - Dobrzhanskiy, Oleksander; Strilchuk, Lyudmyla (Liha-Pres, 2020)
To date, Ukraine-Poland relations are recognized as being a topic of paramount importance in both print and electronic media; it has become a matter of special interest to ordinary citizenry in both Poland and Ukraine. In addition, it is quite justifiable, because since the late 90s of the twentieth century the Republic of Poland, bordering on Ukraine, has become its reliable strategic partner. Remarkable features of the established Ukraine-Poland relations are developing mutually beneficial economic cooperation, building effective political momentum, having geographical proximity, cultural and language similarities, as well as the presence of a large Ukrainian national minority in Poland and the Polish one in Ukraine respectively.
Keywords: Ukraine-Poland relations, mentality, political elites, historical memory